Errors in The Use of Conjunctions in News Texts by Seventh Grade Students at Colomadu Public Junior High School 3 - Karizta Putri Salekha; M Markhamah (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the types of errors in the use of conjunctions in news texts written by seventh-grade students at Colomadu Public Junior Hingh School 3. This study uses a qualitative descriptive approach with research data in the form of sentences in news texts written by seventh-grade students that show errors in the use of conjunctions. Data were collected through observation, documentation, and listening-note-taking techniques, then analyzed using the agih (distribution) method with the BUL (Direct Element Distribution) technique and the ganti (replacement) technique. The results showed that out of 10 news texts written by students, there were 14 sentences containing errors in the use of conjunctions, namely 4 sentences containing the coordinating addition conjunction